2011
DOI: 10.1167/iovs.10-6368
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of Mitochondrial Matrix Metalloproteinase-2 in the Development of Diabetic Retinopathy

Abstract: Elevated MMP2 in the mitochondria degrades its membranes by modulating Hsp60 and damaging connexin 43, and this activates the apoptotic machinery. Better understanding of MMP2-mediated mitochondrial damage could help identify new strategies for the treatment of this blinding disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 38 publications
3
87
0
1
Order By: Relevance
“…Studies have also demonstrated that retinal endothelial cell exposed to high glucose caused a profound increase in the expression of MMP-2 and -9 [45]. This is further supported by our previously published work from transgenic mice that are overexpressing the antioxidant enzyme superoxide dismutase (an antioxidant responsible for superoxide elimination) able to prevent the upregulation of MMP-2 in diabetic retina [36]. Transgenic MMP-9 Knockout mice showed enhanced retinal protection against oxidative stress and reduced apoptosis after diabetes.…”
Section: Mmps and Oxidative Stresssupporting
confidence: 59%
See 3 more Smart Citations
“…Studies have also demonstrated that retinal endothelial cell exposed to high glucose caused a profound increase in the expression of MMP-2 and -9 [45]. This is further supported by our previously published work from transgenic mice that are overexpressing the antioxidant enzyme superoxide dismutase (an antioxidant responsible for superoxide elimination) able to prevent the upregulation of MMP-2 in diabetic retina [36]. Transgenic MMP-9 Knockout mice showed enhanced retinal protection against oxidative stress and reduced apoptosis after diabetes.…”
Section: Mmps and Oxidative Stresssupporting
confidence: 59%
“…We, along with others, have shown that retinal cells incubated in high glucose upregulate the MMP-2 and -9 expression/activation, and inhibition of MMP-2 and -9 is able to prevent high glucose-induced retinal capillary cell apoptosis. Furthermore, we have also shown that high glucose translocate MMP-2 and -9 into the mitochondria and induce mitochondria dysfunction, and inhibition of MMP-2 and -9 ameliorate the high glucose-induced mitochondria dysfunction [23,24,26,35,36]. Hyperglycemia can lead to the activation of MMP-2 and -9 by oxidative stress, MAP kinase pathways [23,26,37].…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Positive controls consisting of retinal vessel exposed to DNAse before initiation of the TUNEL reaction were run simultaneously. After counting the number of TUNEL-positive capillary cells, the slides were stained with periodic acid-Schiff and hematoxylin for histologic evaluation, and the number of acellular capillaries was counted in multiple midretinal fields and expressed per square millimeter of retinal area examined [18,20,23].…”
Section: Gene Expressionmentioning
confidence: 99%